Pengaruh Pemahaman Ilmu Tajwid Terhadap Kemampuan Membaca Al-Qur'an Pada Siswa Madrasah Tsanawiyah - Amirotun Nisa'; Nurul Hidayah; Chusnul Chotimah (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study aims to determine the improvement of students’ Qur’anic reading ability after tajwid instruction and to analyze the effect of tajwid comprehension on students’ Qur’anic reading ability. Methodology/approach: This study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The participants consisted of 51 students from grades VII–IX at MTs Rahmat Sa’id Bongkot Peterongan Jombang. Data were collected through pre-tests, post-tests, and Qur’anic reading practice tests. Data analysis was conducted using paired sample t-test and simple linear regression with the assistance of IBM SPSS version 26. Findings: The results showed a significant improvement in students’ Qur’anic reading ability after tajwid instruction. The mean pre-test score increased from 70.20 to 81.67 in the post-test, with an improvement percentage of 16.34% (t = 9.258; p < 0.05). Simple linear regression analysis indicated that tajwid comprehension had a positive and significant effect on Qur’anic reading ability (β = 0.454; p = 0.016). These findings indicate that better understanding of tajwid rules contributes to better Qur’anic reading ability among students. Practical implications: Schools should implement systematic tajwid instruction accompanied by continuous evaluation and regular Qur’anic reading practice to improve students’ Qur’anic reading ability. Originality/value: Previous studies generally focused on the effectiveness of specific tajwid teaching methods. This study specifically positions tajwid comprehension as the main variable influencing Qur’anic reading ability through the measurement of both theoretical understanding and practical reading skills among Islamic junior high school students.